Language Tokens to Convey Stillness and Silence of Nature in Lesia Ukrainka's Drama «Forest Song» (Linguostylistic Studies, 2018)
The article considers the concept of silence as a non-verbal means of communication, focusing on the peculiarities of silence revelation in the dramatic text and accounting for the multidimensional nature of this phenomenon. The basic lexemes range of the concept of silence in Lesia Ukrainka's drama-fairy tale Forest Song is in the focus of the research. The study elucidates the linguistic reflection specifics of this concept in the drama and determines the communicative preconditions of it, the semantic structure and the stylistic functions of the lexemes expressing the state of muteness or silence. To convey the notion of silence in drama “Forest Song” Lesia Ukrainka uses the following grammatical classes of lexemes: nouns (silence, in silence, pause, stillness, muteness); adverbs (silently, keeping silent); verbs in the present simple tense (keeps silence, contemplates, interrupts, ponds, calms down, etc.). The lexemes denoting silence are attributed by adjectives that semantically specify them: short silence, long silence. Voicelessness is also rendered by kinesics components. For example: shrug, turn away, and so on.The peculiarity of manifestation of silence in the dramatic text is, first of all, the fact that it is actualized not only in replicas of actors but also in the author's remarks. The study has revealed that the phenomenon of silence is closely related to the features of emotional stress. Lesia Ukrainka's characters are experiencing different emotional states accompanied by silence.Nature in the “Forest Song” is personified. It lives in the symbolic images of the play. They are primarily the subjects of fauna and flora. Lesya Ukrainka’s “Silence of Nature” renders silence as stillness with the help of verbs sleeps, calms down, dies; adverbs: quieter, silently, quietly. The writer semantically expands the descriptive patterns of «silence» with such tokens: complete silence, completely calm, completely silent, deep northern silence. Lexical elements that spell out the absence of verbal communication convey different emotional states of heroes. Nonverbal communication means in Lesia Ukrainka's drama fall into the category of frequent elements with distinct compositional and semantic loading.
Keywords: non-verbal communication; silence; stillness; Human Silence; Nature Silence; verbalization; personification